2016
DOI: 10.1002/adsc.201600521
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Alkoxycarbonylation of Alkynes by Means of Aryl α‐Diimine Palladium(II) Complexes as Catalysts

Abstract: Abstract. The straightforward in situ synthesized Bis-(2,6-diisopropyl)-acenaphthenequinonediimine palladium triflate catalyst was generally employed for both the monoalkoxycarbonylation of terminal alkynes, and the bisalkoxycarbonylation of 1,2-disubstituted alkynes by using mild reaction conditions (P CO = 4 bar, Temp. 20°C). Utilizing low catalyst loading (down to 0.5 mol%), a variety of propiolic esters were synthesized with good to excellent isolated yields. Most importantly the system was very efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…[8] To our knowledge, only Nozaki et al showed, in the regiocontrolled copolymerization process of methyl acrylate with CO, that it is possible to carbonylate both the α-and the β-positions of acrylic esters, using a phosphineÀ sulfonate palladium catalyst (Scheme 1b). [10] The catalyst was based on the combination of a palladium salt with bis(aryl)acenaphthenequinonediimine (BIAN) or 1,4diaryl-2,3-diazabutadiene ligands. [10] The catalyst was based on the combination of a palladium salt with bis(aryl)acenaphthenequinonediimine (BIAN) or 1,4diaryl-2,3-diazabutadiene ligands.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] To our knowledge, only Nozaki et al showed, in the regiocontrolled copolymerization process of methyl acrylate with CO, that it is possible to carbonylate both the α-and the β-positions of acrylic esters, using a phosphineÀ sulfonate palladium catalyst (Scheme 1b). [10] The catalyst was based on the combination of a palladium salt with bis(aryl)acenaphthenequinonediimine (BIAN) or 1,4diaryl-2,3-diazabutadiene ligands. [10] The catalyst was based on the combination of a palladium salt with bis(aryl)acenaphthenequinonediimine (BIAN) or 1,4diaryl-2,3-diazabutadiene ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Recently, we have developed a very efficient catalytic system able to promote the bisalkoxycarbonylation of terminal alkenes, [4e] 1,2-disubstituted olefins [5a] and internal alkynes. [10] The catalyst was based on the combination of a palladium salt with bis(aryl)acenaphthenequinonediimine (BIAN) or 1,4diaryl-2,3-diazabutadiene ligands. Similar Pd(II) com-plexes bearing aryl α-diimine ligands were also used by us in the copolymerization of styrenes with CO, yielding copolymers with a high degree of tacticity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many variations of the parent reaction are known and practiced, [ 1–6 ] such as oxidative carbonylation approaches leading to the synthesis of propiolate esters or maleic diesters. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although olefin polymerization has been their most remarkable application, palladium–diimine complexes are also useful catalysts in different C–C cross‐coupling reactions, such as the Heck reaction, Kumada, Negishi, or Stille reactions, and the Suzuki reaction, as well as carbonylation processes …”
Section: Introductionmentioning
confidence: 99%